Rethinking water for SDG 6 - Sadoff, Claudia W.; Borgomeo, Edoardo; Uhlenbrook, Stefan (Springer, 2020)
The world is not on track to achieve Sustainable Development Goal 6 on clean water and sanitation by 2030. We urge a rapid change of the economics, engineering and management frameworks that guided water policy and investments in the past in order to address the water challenges of our time.